2016
DOI: 10.1371/journal.pone.0163066
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of EBA-175 RII-NG Malaria Vaccine Administered Intramuscularly in Semi-Immune Adults: A Phase 1, Double-Blinded Placebo Controlled Dosage Escalation Study

Abstract: The erythrocyte binding antigen region II (EBA-175 RII) is a Plasmodium falciparum ligand that mediates erythrocyte invasion and is considered an important malaria vaccine candidate. A phase Ia trial in malaria naïve adults living in the United States found the recombinant non-glycosylated vaccine antigen, EBA-175 RII-NG adjuvanted with aluminium phosphate to be safe, immunogenic and capable of inducing biologically active antibodies that can inhibit parasite growth in vitro. The aim of the current study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
16
0
2
Order By: Relevance
“…2017), erythrocyte binding antigen (EBA-175, Phase 1a; Koram et al . 2016) and others reaching clinical trials, but with limited efficacy demonstrated to date (reviewed in Draper et al . 2015; Beeson et al .…”
Section: Introductionmentioning
confidence: 99%
“…2017), erythrocyte binding antigen (EBA-175, Phase 1a; Koram et al . 2016) and others reaching clinical trials, but with limited efficacy demonstrated to date (reviewed in Draper et al . 2015; Beeson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Naturally acquired antibodies against EBA-175 have also been shown to inhibit the binding of its invasive ligands to their receptors on RBCs, and these inhibitory antibodies have been associated with a protective immunity [ 136 ]. Adults vaccinated with this antigen showed that it was well tolerated, safe, and immunogenic [ 137 ].…”
Section: Classical Approaches For Malarial Vaccinesmentioning
confidence: 99%
“…An additional randomized, double-blind, phase Ib study evaluated the safety and immunogenicity of EBA-175 RII NG adjuvanted with aluminum phosphate administered in three doses to 60 semi-immune adults in Ghana (Africa) (Koram et al, 2016). Vaccine concentrations (5, 20, and 80 μg) were well tolerated; however, 38 individuals developed grade 1 and grade 2 adverse reactions during follow-up (no severe AE).…”
Section: Clinical Studies Regarding Blood-stage Malaria Vaccinesmentioning
confidence: 99%
“…Some limitations found in both trials were related to sample size, short/limited follow-up, and differences between immunological response regarding vaccine concentrations between people exposed to malaria and those not exposed to it. More time must thus be dedicated to developing the EBA-175 RII NG vaccine to improve its Ab functionality due to poor P. falciparum growth inhibition as demonstrated in in vitro trials (Koram et al, 2016).…”
Section: Clinical Studies Regarding Blood-stage Malaria Vaccinesmentioning
confidence: 99%